Andrew H. Foote papers - Foote, Andrew H. (Andrew Hull), 1806-1863.; Rush, Madison, active 1845-1847.
Correspondence, letterbooks, manuscript of "Africa and the American Flag" (1854), journals, logbooks, ships' records, and other papers relating principally to Foote's naval career and to trade with Japan, Americans living in or engaged in commerce in China, Civil War naval actions, and Foote's personal life. Documents his cruise aboard the ship John Adams involved in a dispute among missionaries in Hawaii, his command (1842-1843) of the U.S. Naval Asylum, his command (1849-1851) of the U.S. brig Perry, U.S. Navy African Squadron, off the west coast of Africa in a joint effort with Great Britain to suppress the slave trade, and his command (1856-1858) of the sloop-of-war Portsmouth, U.S. East India Squadron, including material relating to the Battle of the Barrier Forts (1856) near Canton (Guangzhou), China. Also includes a journal (1845-1847) kept by Madison Rush on a cruise from New York to China and South America.
Correspondents include James Armstrong, Thomas Biddle, Edward A. Blundell, James C. Dobbin, Samuel F. Du Pont, William A. Graham, Francis H. Gregory, George F. Hastings, Duncan N. Ingraham, John Lenthall, William L. Marcy, Levin M. Powell, William Ballard Preston, George C. Read, Joseph J. Roberts, Joseph Smith, Isaac Toucey, John Tudor, and Daniel Webster.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Armstrong, James, -- 1794-1868 -- Correspondence; Biddle, Thomas, -- 1776-1857 -- Correspondence; Blundell, Edward A. -- Correspondence; Dobbin, James C. -- 1814-1857 -- Correspondence; Du Pont, Samuel Francis, -- 1803-1865 -- Correspondence; Graham, William A. -- 1804-1875 -- Correspondence; Gregory, Francis H., -- 1789-1866 -- Correspondence; Hastings, George F. -- Correspondence; Ingraham, Duncan N. -- 1802-1891 -- Correspondence; Lenthall, John, -- 1807-1882 -- Correspondence; Marcy, William L. -- 1786-1857 -- Correspondence; Powell, Levin M., -- 1800-1885 -- Correspondence; Preston, William Ballard, -- 1805-1862 -- Correspondence; Read, George C. -- 1787-1862 -- Correspondence; Roberts, Joseph J. -- 1809-1876 -- Correspondence; Smith, Joseph, -- 1790-1877 -- Correspondence; Toucey, Isaac, -- 1796-1869 -- Correspondence; Tudor, John, -- active 1840-1850 -- Correspondence; Great Britain. -- Royal Navy; United States. -- Naval Asylum; United States. -- Navy -- Foreign service -- China; United States. -- Navy -- History -- Civil War, 1861-1865.; United States. -- Navy. -- African Squadron; United States. -- Navy. -- East India Squadron; John Adams (Ship); Perry (Brig); Portsmouth (Sloop of war); Americans -- China; Barrier Forts, Battle of the, China, 1856.; Missionaries -- Hawaii; Ship's papers -- 19th century; Slave trade -- Africa, West; Africa, West -- Description and travel; Guangzhou (China); Fort Donelson, Battle of, Tenn., 1862.; China -- Commerce -- United States; Japan -- Commerce -- United States; South America -- Description and travel; Tennessee -- History -- Civil War, 1861-1865.; United States -- Commerce -- History -- 19th century; United States -- Commerce -- China; United States -- Commerce -- Japan; United States -- History -- Civil War, 1861-1865 -- Naval operations; Naval officers